PHUBBING BEHAVIOR AND SATISFACTION OF ROMANTIC RELATIONSHIPS IN EARLY ADULT DATING: A CORRELATIONAL STUDY - Kirey Febriani Ajooba; Krismi Diah Ambarwati (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2023)
Background: Intimacy is essential in a dating relationship, but phubbing behaviour can be hindrance which can ultimately interfere with romantic relationship satisfaction. Phubbing behaviour is ignoring other people by playing on mobile phones. Purpose: This study aims to determine the relationship between phubbing behaviour and romantic relationship satisfaction in early adulthood who are dating. Methods: Used the quantitative correlational method. Determination of the sample using the incidental sampling method involved as many as 107 early adult respondents aged 18-40 years and currently undergoing a dating relationship for at least six months in all regions of Indonesia. The instruments in this study were the Relationship Assessment Scale to measure romantic relationship satisfaction and the Generic Scale of Phubbing to measure phubbing behaviour. This study used the Spearman correlation test. Results: Showed that the correlation coefficient was -0.135 with a significance of 0.083 (p>0.05), meaning that phubbing behaviour has no significant negative relationship with romantic relationship satisfaction in early adulthood dating. Conclusion: Phubbing behaviour is not related to romantic relationship satisfaction. Most respondents have phubbing behaviour and romantic relationship satisfaction at a moderate level. Abstrak Latar Belakang: Keintiman diperlukan dalam hubungan, namun perilaku phubbing dapat menjadi penghalang yang akhirnya dapat mengganggu kepuasan hubungan romantis. Perilaku phubbing yaitu tindakan mengabaikan orang lain dengan cara bermain ponsel. Tujuan: Untuk mengetahui hubungan perilaku phubbing dengan kepuasan hubungan romantis pada dewasa awal yang sedang berpacaran. Metode: menggunakan metode kuantitatif korelasional. Penentuan sampel menggunakan metode sampling insidental dan melibatkan sebanyak 107 responden dewasa awal berusia 18-40 tahun dan sedang menjalani hubungan pacaran minimal 6 bulan di seluruh wilayah Indonesia. Instrumen dalam penelitian ini yaitu Relationship Assessment Scale untuk mengukur kepuasan hubungan romantis dan Generic Scale of Phubbing untuk mengukur perilaku phubbing. Penelitian ini menggunakan uji korelasi spearman. Hasil: Menunjukkan bahwa nilai koefisien korelasi sebesar -0,135 dengan signifikansi 0,083 (p > 0,05), artinya perilaku phubbing tidak memiliki hubungan negatif signifikan dengan kepuasan hubungan romantis pada dewasa awal yang sedang berpacaran. Kesimpulan: Perilaku phubbing tidak berhubungan dengan kepuasan hubungan romantis. Mayoritas responden memiliki perilaku phubbing dan kepuasan hubungan romantis di tingkat sedang.